Inovação em serviços médicos de diagnóstico por imagem no Brasil: um estudo de caso de parceria fornecedor - cliente final - Barberio, Paulo de Tarso (2014)
In the search for competitive advantage, companies in the service sector begin to look with greater attention to the need for innovation as vital to the survival or even to differentiate within the current business landscape. The ability or competence to innovate has become an essential ingredient of the current dynamics of the business segment. Innovation in services is a real phenomenon and is integrated into the services used in everyday people from using mobile internet to the hiring of distance learning. It is no different in medical diagnostic imaging services in Brazil, where companies seek to improve the perception of customers regarding services through new and innovative processes. In this context, the aim of the study was to investigate ways and alternatives for small and medium companies in the medical services diagnostic imaging industry create value from the perpective of customers, providing unique solutions and innovative services. The literature review included the historical evolution of diagnostic medicine, as well as the development of the medical equipment market. Regarding innovation, the study reviewed general aspects of the subject, and then the phenomenon of innovation in services, in particular, the main modes of innovation proposed by Gallouj and Weinstein (1997). The literature considered allows a better view of the possibilities of implementing innovative processes within organizations, as well as widen the debate about what can be considered innovation in services. Thus, the case study, in that it analyzes the entire process of implementing new services, it seems feasible as research into alternative implementation and understanding of the main obstacles commonly found for making changes in organizational culture